MODEL PERENCANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) BERBASIS DIFFERENTIATED INSTRUCTION UNTUK MENGAKOMODASI KEBERAGAMAN GAYA BELAJAR SISWA - Alvin Diki Wahyudi; Nur Faiz Habibah; Mar Syahid (Penerbit Widina, Widina Media Utama, 2026)
This study aims to examine the planning of Islamic Religious Education (PAI) learning based on Differentiated Instruction in accommodating the diversity of students’ learning styles at SMK Salafiyah Darul Falah, as well as to investigate the implementation of the Differentiated Instruction-based PAI learning planning model in enhancing students’ learning engagement at the school. The diversity of students’ characteristics, including differences in visual, auditory, and kinesthetic learning styles, requires teachers to design learning that is adaptive, flexible, and responsive to individual students’ needs. In this context, the Differentiated Instruction approach is considered relevant, as it provides opportunities for teachers to adjust strategies, methods, and learning media according to variations in students’ abilities and learning styles. This research employs a qualitative approach with a descriptive research design. Data collection techniques were conducted through observation, interviews, and documentation to obtain in-depth information regarding the planning and implementation processes of PAI learning based on differentiated instruction. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that the planning of PAI learning based on differentiated instruction is conducted by adjusting the content, process, and learning products according to students’ characteristics and learning styles. Teachers design various learning methods such as discussions, demonstrations, the use of visual media, and practical activities to accommodate differences in students’ learning styles. The implementation of this learning model has been proven to increase students’ learning engagement as they participate more actively in the learning process and demonstrate higher learning motivation. Therefore, the PAI lesson planning model based on differentiated instruction can serve as an effective strategy for creating a more inclusive, participatory, and student-centered learning environment. ABSTRAKPenelitian ini bertujuan untuk mengetahui perencanaan pembelajaran Pendidikan Agama Islam (PAI) berbasis Differentiated Instruction dalam mengakomodasi keberagaman gaya belajar siswa di SMK Salafiyah Darul Falah, serta untuk mengetahui implementasi model perencanaan pembelajaran PAI berbasis Differentiated Instruction dalam meningkatkan keterlibatan belajar siswa di sekolah tersebut. Keberagaman karakteristik peserta didik, termasuk perbedaan gaya belajar visual, auditori, dan kinestetik, menuntut guru untuk merancang pembelajaran yang adaptif, fleksibel, dan responsif terhadap kebutuhan individu siswa. Dalam konteks ini, pendekatan Differentiated Instruction dipandang relevan karena mampu memberikan ruang bagi guru untuk menyesuaikan strategi, metode, serta media pembelajaran sesuai dengan variasi kemampuan dan gaya belajar siswa. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi untuk memperoleh informasi secara mendalam mengenai proses perencanaan dan implementasi pembelajaran PAI berbasis differentiated instruction. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa perencanaan pembelajaran PAI berbasis differentiated instruction dilakukan dengan menyesuaikan konten, proses, dan produk pembelajaran berdasarkan karakteristik dan gaya belajar siswa. Guru merancang berbagai variasi metode pembelajaran seperti diskusi, demonstrasi, penggunaan media visual, serta kegiatan praktik untuk mengakomodasi perbedaan gaya belajar siswa. Implementasi model pembelajaran tersebut terbukti mampu meningkatkan keterlibatan belajar siswa karena mereka lebih aktif berpartisipasi dalam proses pembelajaran dan menunjukkan motivasi belajar yang lebih tinggi. Model perencanaan pembelajaran PAI berbasis differentiated instruction dapat menjadi strategi yang efektif dalam menciptakan pembelajaran yang lebih inklusif, partisipatif, dan berpusat pada siswa.